2019
DOI: 10.3390/ijms20204970
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Variation in the Biological Effects of PM2.5 from Greater Cairo

Abstract: Greater Cairo (Egypt) is a megalopolis where the studies of the air pollution events are of extremely high relevance, for the geographical-climatological aspects, the anthropogenic emissions and the health impact. While preliminary studies on the particulate matter (PM) chemical composition in Greater Cairo have been performed, no data are yet available on the PM’s toxicity. In this work, the in vitro toxicity of the fine PM (PM2.5) sampled in an urban area of Greater Cairo during 2017–2018 was studied. The PM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…Reduction of PM levels during the COVID-19 pandemic has also been observed in several countries/cities including China ( Wang and Su, 2020 ; Wang et al, 2020c ), India ( Sharma et al, 2020 ), Rio de Janeiro ( Dantas et al, 2020 ), São Paulo ( Nakada and Urban, 2020 ), Milan ( Collivignarelli et al, 2020 ), Barcelona ( Tobías et al, 2020 ), Nice, Rome, Valencia and Turin ( Sicard et al, 2020 ). The PM emissions in big cities like Cairo has always been reported to be exceeding the national regulations (230 μg/Nm 3 for 24-hour averaging period) ( Huzayyin and Salem, 2013 ; Hassan and Khoder, 2017 ; Marchetti et al, 2019 ).
Figure 6 Absorbing Aerosol Index for Egypt from March 15 to May 1 for years 2019 and 2020.
…”
Section: Resultsmentioning
confidence: 99%
“…Reduction of PM levels during the COVID-19 pandemic has also been observed in several countries/cities including China ( Wang and Su, 2020 ; Wang et al, 2020c ), India ( Sharma et al, 2020 ), Rio de Janeiro ( Dantas et al, 2020 ), São Paulo ( Nakada and Urban, 2020 ), Milan ( Collivignarelli et al, 2020 ), Barcelona ( Tobías et al, 2020 ), Nice, Rome, Valencia and Turin ( Sicard et al, 2020 ). The PM emissions in big cities like Cairo has always been reported to be exceeding the national regulations (230 μg/Nm 3 for 24-hour averaging period) ( Huzayyin and Salem, 2013 ; Hassan and Khoder, 2017 ; Marchetti et al, 2019 ).
Figure 6 Absorbing Aerosol Index for Egypt from March 15 to May 1 for years 2019 and 2020.
…”
Section: Resultsmentioning
confidence: 99%
“…The study found that this toxicity is linked to the season. Indeed, in warmer-season, possible genotoxic effects appear, while in colder seasons, potential cell xenobiotic responses and pro-inflammatory effects appear [ 73 ].…”
Section: Resultsmentioning
confidence: 99%
“…All analyses were undertaken in triplicate. The limits of detection and quantifications were automatically calculated by the ICP MassHunter software based on the analysis of 16 blanks. , All measurements were greatly in excess of the limits of detection.…”
Section: Methodsmentioning
confidence: 99%